2018
DOI: 10.3390/en11061499
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Small-Scale Adsorption Cooling System Performance Employing Activated Carbon-Ethanol Pair

Abstract: Adsorber heat exchanger design has great importance in increasing the performance of the adsorption-based cooling system. In this study, a transient two-dimensional axisymmetric Computational Fluid Dynamics (CFD) model has been developed for the performance investigation of finned tube type adsorber using activated carbon and ethanol as the working pair. The operating conditions of the cooling system were 15, 20 and 80 for evaporation, cooling and heating temperatures, respectively. The simulated temperature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…A Computational Fluid Dynamics (CFD) model was developed by Khanam et al [29] to assess the performance of a finned tube type adsorber utilising a pair of activated carbon and ethanol. The operating temperatures of the cooling system were 80℃, 20℃ and 15℃ for heating, cooling and evaporation respectively.…”
Section: Figure 3 Adsorption Cooling System With Two Beds [12]mentioning
confidence: 99%
See 1 more Smart Citation
“…A Computational Fluid Dynamics (CFD) model was developed by Khanam et al [29] to assess the performance of a finned tube type adsorber utilising a pair of activated carbon and ethanol. The operating temperatures of the cooling system were 80℃, 20℃ and 15℃ for heating, cooling and evaporation respectively.…”
Section: Figure 3 Adsorption Cooling System With Two Beds [12]mentioning
confidence: 99%
“…The following section discusses the equations of energy balance for the various components of ARS. The equations are written by taking into account the mechanism of heat transfer occurs inside the components and based on the similar studies made by Pinto et al [14], Khanam et al [29], Baiju et al [32], Gado et al [33], Passos et al [37], Sakoda and Suzuki [38], and so on.…”
Section: Energy Balance Equationsmentioning
confidence: 99%
“…Van der Waals forces and hydrophobic interactions produce the attraction (not covalent bonding) [5]. The state of equilibrium is achieved after a protracted period during which adsorbing molecules settle on the adsorbent surfaces [15]. Working pairs for adsorption are typically chosen depending on the temperature of the available heat source and the cooling load [16].…”
Section: Adsorption Equilibriummentioning
confidence: 99%
“…All adsorption models are based on the adsorption equilibrium. The implementation of both kinetic and dynamic adsorption models requires knowledge of the adsorption equilibrium [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies on solar based adsorption by Kairul Habib et al [20], Wissam H. Khaleel [21], N. V. Ogueke et al [22], Khattab et al [23], Hassan et al [24], Mohammed Ali Hadj Ammar et al [25], etc. many theoretical studies were found by researchers like V Baiju et al [26], A. Asif Sha et al [27], H. T. Chua et al [28], Sakoda et al [29], Xiaolin Wang et al [30], Yongling Zhao et al [31], Marzia Khanam et al [32] etc. Research on activated Carbon with different adsorbates such as ethanol, methanol, R-134a etc.…”
Section: Introductionmentioning
confidence: 99%